Pengembangan Penuntun Praktikum Kimia Inovatif Terintegrasi Pembelajaran Berbasis Proyek dan Karakter Pada Materi Koloid - Bajoka Nainggolan; Wesly Hutabarat; Liemmy Gultom (Universitas Negeri Medan, 2019)
Descriptive research and development using the ADDIE method aims to Innovatiive develop project-based and character practical guides of Colloidal material according with BSNP standards. The sample of 2 lecturers and 2 chemistry teachers, practical guides for Erlangga (A), Bumi Aksara (B), Pudak Saintifk (C), 26 students XI IPA-5 (experiment) and 26 students XI IPA-6 (control) at the Medan 3th Senior High School. Data was processed descriptively, obtained the results of feasibility validation contents 3.53; language 3.46; presentation of 3.50, score of 3.53, average of 3.32; it means that the practical guides resulting from the development is very valid according to the BSNP standard. Data analysis with ANOVA, obtained the average scores of student outcomes in experimen > control class or 81.5% > 73.8%. Then the average phsychomotor scores of experimen was larger than control class or 84, 64 > 82.78. In addition, the affective scores of experimen was larger than control class or 78.42 > 76.38. The hypothesis tested with one way ANOVA at the significant level of α 0.05, and found that tcount> ttable, (4.536 > 1.697). It is concluded that the Innovative Chemistry Practicum Guides developped is highly very good, suitable for use in Senior High School.